Chord Newton’s Method for Solving Fuzzy Nonlinear Equations - Usman Moyi, Aliyu (International Journal of Advanced Mathematical Sciences, 2019)
In this paper, we present a new approach for solving fuzzy nonlinear equations. Our approach requires toÂ compute the Jacobian matrix once throughout the iterations unlike some Newtonâ€™s-like methods which needs to compute the Jacobian matrix in every iterations. The fuzzy coefficients are presented in parametric form. Numerical results on well-known benchmarks fuzzy nonlinear equations are reported to authenticate the effectiveness and efficiency of the approach.